Satisfaction of Pregnant Women in Antenatal Care Service Attending in Province Hospital Surkhet, Karnali province, Nepal - Sapkota, Shakuntala; Pant, Pratima Kumari; Khadka, Damber; Chaudhari, Aitawari (NPRC Journal of Multidisciplinary Research, 2026)
Introduction: Antenatal care is the comprehensive health checkup and counselling provided to pregnant women from conception until the onset of labor. Regular antenatal care (ANC) is necessary for the early detection and prevention of pregnancy-related complications and ensures timely management of maternal health problems. Evaluating the satisfaction of pregnant women with ANC services is essential to distinguish gaps between expected and received care. Hence, this study aims to investigate the status and influencing factors of satisfaction with antenatal care among pregnant women in province hospital Surkhet, Nepal. Methods: A descriptive cross-sectional study was conducted for the study. A non-probability convenience sampling method was used to select 246 pregnant women who had completed at least three antenatal care visits at ANC clinic of province hospital, Surkhet, Karnali Province, Nepal. A self-made general information questionnaires and antenatal care satisfaction questionnaires were used for data collection from November 2024 to May 2025. ANOVA and Kruskal-Wallis H test were used for the single-factor analysis of satisfaction of pregnant women with antenatal care service, and multiple linear regression was used for the multi-factor analysis. Results: The overall antenatal care satisfaction score among respondents was 80.57+8.32, which indicates a moderate level of satisfaction. Dimensions-wise mean scores were: attitude of health care providers (18.97 ± 2.53), humanistic care (18.21 ± 2.50), health facilities and environment (16.50 ± 2.40), health instruction (15.06 ± 2.26) and professional skills (11.84 ± 1.73). The results of bivariate analysis showed that pregnant women with different education levels and economic status (P<0.05) were statistically significant with antenatal care satisfaction. The results of multiple linear regression analysis showed that economic status, means of transportation, occupation and number of children were the influencing factors of antenatal care satisfaction of pregnant women (P<0.10). Conclusion: The study found that pregnant women had a moderate level of satisfaction with antenatal care services, suggesting that existing health services do not fully meet their expectations and needs. Enhancing accessibility, affordability, service quality, and client-centered care-particularly for socio-economically disadvantaged group is necessary to improve maternal satisfaction and health related outcomes.